Qualitative analysis of two systems of nonlinear first‐order ordinary differential equations for biological systems. (10th January 2022) - Wacker, Benjamin; Schlüter, Jan Christian
Abstract : We consider two systems of nonlinear first‐order ordinary differential equations proposed to describe Ca 2 + ‐levels in renal vascular smooth muscle cells and in liver cells. Initially, we present the models and its assumptions. We next investigate an approach to local solvability by Picard–Lindelöf 's Theorem. Further, we prove nonnegativity of the systems' possible solutions and we especially conclude global unique existence of the models' solutions by Gronwall‐type arguments and the concept of trapping regions. After finishing our theoretical part with some aspects of stability analysis, we provide evidence of our findings by some numerical experiments.